December 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)

November 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)

[Newsletter] - 4 Korners Family Resource Center (2023)

Seniors Action Quebec E-Newsletter - Seniors Action Quebec (SAQ) (2023)

[Newsletter] - 4 Korners Family Resource Center (2023)

[Newsletter] - 4 Korners Family Resource Center (2023)

June 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Seniors Action Quebec Presentation on Study Matters Relating to Minority-Language Health Services - Seniors Action Quebec (SAQ) (2023)

May 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)

VISION : Bulletin for health and wellbeing - Vision Gaspé-Percé Now (2023)

Seniors Action Quebec Brief : Vieillir et vivre ensemble, chez soi, dans sa communauté, au Québec (VVE) - Plan d’action 2024-2029 - Seniors Action Quebec (SAQ) (2023)

April 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

Make the Case Report : Access to Senior Care in English in Quebec : A research analysis of English language rights in Quebec health care and access to the SAPA program for English-speaking seniors in Quebec - Quebec Community Groups Network (QCGN) (2023)
This report discusses and details one of the AJEQ Project’s candidate issues of research: access to senior health care services in English in Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Projet Accès à la justice en anglais : Services de soins aux personnes âgées en anglais au Québec : Sommaire du rapport final et recommandations au Ministère de la Santé et des Services sociaux - Quebec Community Groups Network (QCGN) (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations of the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

CHSSN Senior Wellness Centre Initiative Activity Report Year 2 (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Senior Wellness Centre Initiative Activity Report (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Spring 2023 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2023)

Annual Report 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Rapport annuel 2022-2023 - Seniors Action Quebec (SAQ) (2023)

The Yellow Door : 2022-2023 Annual Report / La Porte Jaune : 2022-2023 Rapport annuel - Yellow Door (2023)